Medi_Link: A Digital Health Platform Enhancing Maternal Care in Rural Uganda - Deogratius Baligeya; Jane Evans Sande (Uganda Christian University, 2025)
Medi_Link is a digital health platform developed to improve maternal health in rural Uganda by addressing challenges such as poor healthcare access, infrastructure limitations, and shortages of skilled professionals. Key features include virtual consultations, personalized health tips, emergency first aid guidance, and digital medical records. Built with technologies like React, Vite, and TypeScript, it supports low-bandwidth and offline use to suit rural conditions. The platform promotes remote care, continuity in maternal health, and aims to reduce maternal mortality and improve healthcare experiences for mothers and children.
Medi_Link is an innovative digital health platform developed to address the critical challenges of maternal healthcare in rural Uganda. The platform is designed to enhance access to quality medical services for expectant mothers in underserved areas by offering virtual consultations, personalized health advice, emergency first aid guidance, and secure digital storage of medical records. Leveraging modern web technologies such as React, Vite, and TypeScript, Medi_Link delivers a user-friendly and responsive experience tailored to both healthcare providers and patients. The system is optimized for low-bandwidth environments and includes offline functionality to accommodate areas with poor internet connectivity. By bridging the gap between remote communities and professional healthcare services, Medi_Link aims to reduce maternal mortality rates, promote continuous health monitoring, and significantly improve maternal and child health outcomes in Uganda.